Comparison of Carcinoembryonic Antigen Serum Levels in Colorectal Cancer Patients with Different Histopathological Grades - Chandra Agusrly; Taufik Sungkar; Gontar Alamsyah Siregar (Majalah Kedokteran Bandung, 2020)
Histopathological grading, which represents the degree of histopathological differentiation, is often used as one of the factors to determine the prognosis of colorectal cancer. However, this grading cannot comprehensively present the clinical features of the disease. Carcinoembryonic antigen (CEA), as a tumor marker tested in the laboratory, is commonly used to determine the diagnosis and prognosis of colorectal cancer. The purpose of this study was to determine differences in CEA serum levels based on the cellular differentiation of colorectal cancer. This was a cross-sectional analytical study on medical records of colorectal cancer patients who were admitted to H. Adam Malik General Hospital Medan, Indonesia from January 2016 to December 2018. As many as 52 medical records of colorectal cancer patients who met the inclusion and exclusion criteria were included in this study. These patients were then divided into three groups based on the histopathological grade: well-differentiated, moderately differentiated, and poorly-differentiated. The Kruskal-Wallis test was then used to compare the CEA levels in these different histopathological grades. Results show that the CEA serum level was different in colorectal cancer patients with different histopathological grades (p=0.020). The CEA level was significantly higher in the poorly-differentiated group than the well-differentiated (p=0.044) and moderately differentiated (p=0.015) groups. Hence, the CEA level of colorectal cancer patients with poorly-differentiated grade is the highest when compared to other grades. Perbandingan Kadar Serum Carcinoembryonic Antigen Berdasar atas Derajat Histopatologi Pada Pasien Kanker Kolorektal Derajat diferensiasi dapat dijadikan sebagai salah satu faktor prognosis pada kanker kolorektal. Namun, penilaian ini tidak dapat menyajikan gambaran klinis penyakit secara komprehensif. Penanda tumor carcinoembryonic antigen (CEA) sebagai penanda tumor yang diuji di laboratorium, umumnya digunakan untuk menentukan diagnosis dan prognosis kanker kolorektal. Tujuan dari penelitian ini adalah menentukan perbedaan kadar serum CEA berdasar atas diferensiasi sel kanker kolorektal. Penelitian ini merupakan penelitian analitik dengan desain bedah lintang dengan menggunakan data rekam medis pasien yang didiagnosis kanker kolorektal di Rumah Sakit Umum Pusat H. Adam Malik, Medan periode Januari 2016 hingga Desember 2018. Sebanyak 52 catatan medis pasien kanker kolorektal yang memenuhi inklusi dan kriteria eksklusi dimasukkan dalam penelitian ini. Derajat diferensiasi dikelompokkan menjadi tiga: derajat baik, sedang, dan buruk. Uji Kruskal-Wallis digunakan untuk membandingkan kadar CEA berdasar atas derajat diferensiasi. Hasil menunjukkan bahwa kadar serum CEA berbeda pada pasien kanker kolorektal dengan nilai histopatologis yang berbeda (p=0,020). Tingkat CEA secara signifikan lebih tinggi pada kelompok berdiferensiasi buruk daripada kelompok berdiferensiasi baik (p=0,044) dan kelompok berdiferensiasi sedang (p=0,015). Oleh karena itu, tingkat CEA pasien kanker kolorektal dengan derajat diferensiasi buruk adalah yang tertinggi jika dibandingkan dengan tingkat lainnya.